Preliminary Interpretation of the Ground Magnetic Survey around Oguta Lake in Imo State, South Eastern Nigeria - FI Chinyem (Journal of Applied Sciences and Environmental Management)
Ground magnetic profiling was carried out around Oguta Lake in Imo State, Southeastern Nigeria. Seventy-Six stations in three profiles were established at five hundred meters intervals on major roads in the study area, A total distance of thirty five kilometers was covered. The result indicates that the highest field reading was 32835gamma while the lowest field was 28118gamma. Five anomalies were observed. The anomaly at the lake, was most prominent with magnetic readings of 28118 -29235 gamma and elevations of 17 -37 feet, all treading in the NE –SW direction. These anomalies, suggest that the lake has a tectonic origin. @JASEM